2020
DOI: 10.1155/2020/8787153
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Xu Li’s Experiential Prescription for the Treatment of EGFR‐Positive NSCLC

Abstract: The non-small-cell lung cancer (NSCLC) is the most common lung cancer which seriously threatens the human health. Xu Li’s experiential prescription (XLEP) can treat the NSCLC. However, whether XLEP can regulate the autophagy in the EGFR-positive NSCLC still remains unknown. We found that the cellular activity of drug-resistant cells and sensitive cells were all decreased in the TCM group and TCM + Gef group. The expression of autophagy-associated proteins (mTOR and Beclin1-Vps34) in drug-resistant cells was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Xu Li’s experiential prescription (XLEP) has been applied in the treatment of NSCLC, which is mainly composed of Radix adenophorae , Radix Glehniae , Radix Asparagi , Radix Ophiopogonis , Schisandra , Privet fruit , Astragalus , Zedoary . Xu et al 189 discovered that XLEP could promote M2-like macrophage polarization to M1-like macrophages and increase the M1-like /M2-like macrophage ratio in EGFR-positive NSCLC cells. This effect was mediated by the downregulation of mTOR, IL-10, TGF-β, and CCL22 and the upregulation of IL-6, CCL2, CCL3, and TNF-α, thereby delaying resistance to the EGFR-TKI inhibitor gefitinib.…”
Section: Targeting M2-like Tams To Overcome Tumor Resistancementioning
confidence: 99%
“…Xu Li’s experiential prescription (XLEP) has been applied in the treatment of NSCLC, which is mainly composed of Radix adenophorae , Radix Glehniae , Radix Asparagi , Radix Ophiopogonis , Schisandra , Privet fruit , Astragalus , Zedoary . Xu et al 189 discovered that XLEP could promote M2-like macrophage polarization to M1-like macrophages and increase the M1-like /M2-like macrophage ratio in EGFR-positive NSCLC cells. This effect was mediated by the downregulation of mTOR, IL-10, TGF-β, and CCL22 and the upregulation of IL-6, CCL2, CCL3, and TNF-α, thereby delaying resistance to the EGFR-TKI inhibitor gefitinib.…”
Section: Targeting M2-like Tams To Overcome Tumor Resistancementioning
confidence: 99%
“… 22 As an auxiliary and complementary medicine in China, traditional herbal medicine is prevalently used in clinical practice. 23 , 24 Traditional herbal medicine has the advantages of alleviating clinical symptoms, enhancing autoimmunity and helping to manage the quality of life of patients. 25 - 27 Previous studies have reported that herbal extracts and prescriptions through multi-targeting inhibit tumor proliferation, induce tumor apoptosis, and alleviate drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…CHM contains several active compounds that interact with target proteins involved in EGFR-TKI resistance (Bing et al, 2018), in addition to enhancing the inhibition effect of EGFR-TKIs in gefitinibresistant NSCLC cells by activating PI3-K/Akt-mediated suppress of MUC1 expression (Li et al, 2016). CHM has also been reported to increase the ratio of M1/M2 macrophages by inhibiting autophagy, and suppress the proliferation of EGFR-TKI-resistant cancer cells (Xu et al, 2020). Several clinical trials and systematic reviews report that CHM is effective in delaying EGFR-TKI resistance and alleviating AE (.…”
Section: Introductionmentioning
confidence: 99%